2022
DOI: 10.1186/s13023-021-02068-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into PORCN mutations, associated phenotypes and pathophysiological aspects

Abstract: Background Goltz syndrome (GS) is a X-linked disorder defined by defects of mesodermal- and ectodermal-derived structures and caused by PORCN mutations. Features include striated skin-pigmentation, ocular and skeletal malformations and supernumerary or hypoplastic nipples. Generally, GS is associated with in utero lethality in males and most of the reported male patients show mosaicism (only three non-mosaic surviving males have been described so far). Also, precise descriptions of neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(54 reference statements)
2
5
0
Order By: Relevance
“…Immunoblot studies on whole proteins extracts of the PPP1R21-patient and two pooled controls were carried out as described previously [ 15 ] utilizing the primary antibodies listed in supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot studies on whole proteins extracts of the PPP1R21-patient and two pooled controls were carried out as described previously [ 15 ] utilizing the primary antibodies listed in supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…3 Developmental abnormalities of the eye (include a spectrum of anomalies of the lacrimal glands, iris and retina) are often associated with craniofacial findings, and skeletal abnormalities include limb malformation syndactyly and/or ectrodactyly. 4 Psychomotor development is usually normal. 2,4,5 All these anomalies show a segmental arrangement reflecting functional X-chromosome mosaicism.…”
Section: Reportmentioning
confidence: 99%
“…Skin manifestations present at birth include hypoplastic areas of skin and the syndrome is also known as FDH 3 . Developmental abnormalities of the eye (include a spectrum of anomalies of the lacrimal glands, iris and retina) are often associated with craniofacial findings, and skeletal abnormalities include limb malformation syndactyly and/or ectrodactyly 4 . Psychomotor development is usually normal 2,4,5 .…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Although germline-derived pathogenic variants in PORCN (porcupine O-acyltransferase) on Xp11.23 are known to cause focal dermal hypoplasia (FDH) (alias, Goltz-Gorlin syndrome) (OMIM #305600) recognized as an apparently X-linked dominant male-lethal disorder (Bostwick et al, 2016), recent studies have revealed that several germline-derived PORCN variants lead to an apparently X-linked recessive disorder, with an abnormal phenotype in hemizygous males and a normal phenotype in heterozygous females (Arlt et al, 2022;Brady et al, 2015;Madan et al, 2017;Wawrocka et al, 2021).…”
Section: To the Editormentioning
confidence: 99%